2021
DOI: 10.3390/plants10050850
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Expression Profiles of the Dof Family in Cleistogenes songorica under Temperature, Salt and ABA Treatment

Abstract: The DNA-binding with one zinc finger (Dof) family of plant-specific transcription factors has a variety of important functions in gene transcriptional regulation, development, and stress responses. However, the structure and expression patterns of Dof family have not been identified in Cleistogenes songorica, which is an important xerophytic and perennial gramineous grass in desert grassland. In this study, 50 Dof genes were identified in C. songorica and could be classified into four groups. According to geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have indicated that most plant TFs are localized to the nucleus, and play their regulatory role ( Wang et al., 2015 ; Wu et al., 2017 ; Ren et al., 2020 ), and our results are consistent with these studies. In Cleistogenes songorica , the expression of Dof genes can respond to high/low temperature, salinity, and ABA treatment ( Wang et al., 2021a ). In Spirodela polyrhiza , the expression patterns of SpWRKYs under phosphate starvation, cold, and submergence treatment indicate that most SpWRKYs are involved in the response to different types of abiotic stress ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that most plant TFs are localized to the nucleus, and play their regulatory role ( Wang et al., 2015 ; Wu et al., 2017 ; Ren et al., 2020 ), and our results are consistent with these studies. In Cleistogenes songorica , the expression of Dof genes can respond to high/low temperature, salinity, and ABA treatment ( Wang et al., 2021a ). In Spirodela polyrhiza , the expression patterns of SpWRKYs under phosphate starvation, cold, and submergence treatment indicate that most SpWRKYs are involved in the response to different types of abiotic stress ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several genes are involved in the regulation of stress responses. Transcription factors (TFs) can bind to specific cis - acting elements on promoters to control the expression of various target genes; they thus play important roles in the growth and development of plants ( Franco-Zorrilla and Solano, 2017 ; Wang et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA-binding with one finger (Dof) proteins are a group of plant-specific TFs [ 3 ]. Following the isolation of the first Dof gene ( Zmdof1 ) from maize, additional Dof genes have been identified in other plants and are the subject of extensive research [ 4 , 5 , 6 , 7 , 8 ]. In N-terminal regions, the Dof proteins contain a highly conserved Dof domain (about 52 amino acids with a Cys2/Cys2 zinc finger structure).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 54, 31, 28, and 24 Dof family members were predicted in monocots such as Zea mays [14], Triticum aestivum [15], Sorghum bicolor [16], and Hordeum vulgare [17], respectively, while 36, 41, 89, and 78 Dof family members were predicted in dicots such as Arabidopsis thaliana [13], Populus trichocarpa [18], Gossypium hirsutum [19], and Glycine max [20], respectively. Previous studies have demonstrated that Dof transcription factors are involved in regulating plant growth [21][22][23][24][25], and more recently, they have been found to play a crucial role in the plant's response to abiotic stresses [26][27][28][29]. For example, Dof genes in moso bamboo have been shown to be involved in cold, salt, and drought stress responses [30].…”
Section: Introductionmentioning
confidence: 99%